Effect of fish meal replacement with lentil seed (Lens culinaris) in common carp (Cyprinus carpio) L. diet - Nasreen Mohialddin Abdulrahman; Vian Muhamad Ahmad; Bakhan Rafiq Hassan; Zaweta Sharif Abdulla; Derin Omer Muhammed-Ramzi; Hevar Aras Hama-Salih; Hemin Nuraddin Mohammed (Journal Omni-Akuatika, 2021)
The aim of this study was to see how replacing fish meal with lentil seeds (LS) as an alternative plant protein source in diets for common carp Cyprinus carpio affected growth performance, feed consumption, and the composition of the fish's proximate carcass. The fish (100-106 g mean initial weight) were fed 0% (LS0), 5% (LS5), 10% (LS10), 15% (LS15) and 20% (LS20) of Lentil seed protein for 10 weeks. With increasing fishmeal replacement with lentil seed in the fish diet, there was a significant (p<0.05) increase in weight gain, relative and specific growth rate. T5 (20% LS) had a significantly (p<0.05) higher feed efficiency ratio and protein efficiency ratio than the other treated groups. There were no significant (p<0.05) differences in the mean values of proximate composition of fish fillets, such as moisture, crude protein, crude lipid and ash. Finally, no significant differences in muscle ratio (weight without viscera vs. weight without viscera & head) were found. The current study found that lentil seed can replace 20% of dietary fish meal in common carp diets for better growth.Keywords: lentil seed, fish meal, common carp, growth performance and feed utilization.